2017
DOI: 10.1177/0959683617693902
|View full text |Cite
|
Sign up to set email alerts
|

Size changes in wild and domestic pig populations between 10,000 and 800 cal. BC in the Iberian Peninsula: Evaluation of natural versus social impacts in animal populations during the first domestication stages

Abstract: In the early-Holocene, animal domestication processes entailed important changes to the subsistence strategies of Neolithic populations. Among the first domestic species, pigs played a key role as they soon came to be one of the main sources of meat. Several methodological approaches have been followed in archaeology to differentiate between wild and domestic forms in the faunal remains found at early Neolithic sites. Among these, biometry is essential. The biometric analysis applied to a significant sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…Although the presence of crops in La Draga is clear (Antolín, ; Antolín and Buxó, ;), the increase in δ 15 N values is quite low to propose an intensive manuring effect (Bogaard et al, ). However, the other Early Neolithic site, Cova de Frare, presents no isotopic differences between wild and domestic herbivores (Navarrete et al, ), likewise as observed at Cueva de Chaves.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Although the presence of crops in La Draga is clear (Antolín, ; Antolín and Buxó, ;), the increase in δ 15 N values is quite low to propose an intensive manuring effect (Bogaard et al, ). However, the other Early Neolithic site, Cova de Frare, presents no isotopic differences between wild and domestic herbivores (Navarrete et al, ), likewise as observed at Cueva de Chaves.…”
Section: Discussionmentioning
confidence: 90%
“…Isotopic tests between wild and domestic herbivores have been carried out in order to test differences in husbandry management practices in other contemporary Iberian sites such as La Draga or Cova de Frare (Navarrete et al, ). At the first site, the domestic fauna showed higher δ 13 C and δ 15 N values (Navarrete et al, ). These slight isotopic differences could suggest different feeding strategies, such us using agricultural crops as one of the potential fodders for domestic species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations